2016
DOI: 10.1016/j.matbio.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of Dspp partially rescued the long bone defects of Dmp1-null mice

Abstract: Dentin matrix protein 1 (DMP1) and dentin sialophosphoprotein (DSPP) belong to the Small Integrin-Binding Ligand N-linked Glycoprotein (SIBLING) family. In addition to the features common to all SIBLING members, DMP1 and DSPP share several unique similarities in chemical structure, proteolytic activation and tissue localization. Mutations in, or deletion of DMP1, cause autosomal recessive hypophosphatemic rickets along with dental defects; DSPP mutations or its ablation are associated with dentinogenesis imper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…In detail, DSP, DSPP, and DMP1 are responsible for dentin formation and the precisely oriented hydroxyapatite crystals initiation in calcifying matrices [32]. DSPP may act as a downstream effector molecule of DMP1 during dentinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, DSP, DSPP, and DMP1 are responsible for dentin formation and the precisely oriented hydroxyapatite crystals initiation in calcifying matrices [32]. DSPP may act as a downstream effector molecule of DMP1 during dentinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin matrix protein-1 (DMP1) is expressed in odontoblasts that secrete the matrix proteins in the process of dentinogenesis and mineralization during postnatal tooth development. Some studies have suggested a potential functional and synergistical relationship between DSPP and DMP1 , in which DSPP acts as the downstream effector molecule of DMP1 and can be controlled by DMP1 during the dentinogenesis and osteogenesis272829.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lyses containing equal amount of β-actin were loaded onto 5–15% SDS-PAGE to follow the protocol as previously described [13]. The the primary antibody against FGF23 was monoclonal mouse IgG [14]. The antibodies against the phosphorylated and total phosphorylated Smad1/5/8, p-38 and Erk were all polyclonal rabbit IgG purchased from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%